Doppler Wind Lidar From UV to NIR: A Review With Case Study Examples - Shangguan, Mingjia; Qiu, Jiawei; Yuan, Jinlong; Shu, Zhifeng; Zhou, Lingfeng; Xia, Haiyun (Frontiers in Remote Sensing, 2022)
Doppler wind lidar (DWL) uses the optical Doppler effect to measure atmospheric wind speed with high spatial-temporal resolution and long detection range and has been widely applied in scientific researches and engineering applications. With the development of related technology, especially laser and detector technology, the performance of the DWL has significantly improved for the past few decades. The DWL utilizes different principles and different tracers to sense the wind speed from the ground to the mesosphere, which leads to the difference in choosing the laser working wavelength. This article will review the working wavelength consideration of DWL, and typical DWLs will present from ultraviolet to near-infrared, after that, three typical applications will be shown.